2010
DOI: 10.1111/j.1469-1795.2010.00366.x
|View full text |Cite
|
Sign up to set email alerts
|

Ranging behavior and habitat selection of terrestrial insectivorous birds in north‐east Tanzania: implications for corridor design in the Eastern Arc Mountains

Abstract: Understanding the ranging behavior and habitat selection of understory tropical birds is important for corridor design and enhancing functional connectivity in fragmented tropical landscapes. Here we report on the ranging behavior and habitat selection of three terrestrial insectivorous bird species, the spot-throat Modulatrix stictigula, Usambara thrush Turdus roehli and orange ground thrush Zoothera gurneyi, in the East (EUM) and West (WUM) Usambara Mountains in north-east Tanzania. Based on 5945 locations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 40 publications
(74 reference statements)
2
23
0
Order By: Relevance
“…Mountains, Tanzania (Newmark et al 2010). However, also in this latter study, most individuals avoided crossing non-forested openings (Newmark et al 2010).While our short-term ecological data suggest a high site-fidelity of the three study birds, genetic data imply a moderate exchange of individuals, sufficient to equilibrate the genetic structure over local populations, as indicated for Z. poliogaster mbuluensis over the Chyulu Hills (Habel et al 2014a, b), as well as for A. milanjensis and P. stellata macarthuri for the adjoining Taita Hills (Callens et al 2011). Studies showed that only few individuals per generation (as observed for Z. poliogaster mbuluensis) are sufficient to balance genetic differentiation (Slatkin 1987).…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…Mountains, Tanzania (Newmark et al 2010). However, also in this latter study, most individuals avoided crossing non-forested openings (Newmark et al 2010).While our short-term ecological data suggest a high site-fidelity of the three study birds, genetic data imply a moderate exchange of individuals, sufficient to equilibrate the genetic structure over local populations, as indicated for Z. poliogaster mbuluensis over the Chyulu Hills (Habel et al 2014a, b), as well as for A. milanjensis and P. stellata macarthuri for the adjoining Taita Hills (Callens et al 2011). Studies showed that only few individuals per generation (as observed for Z. poliogaster mbuluensis) are sufficient to balance genetic differentiation (Slatkin 1987).…”
mentioning
confidence: 83%
“…To analyse potential differences in daily activity we created the following temporal cohorts: morning (8h00-11h00), midday (11h00-14h00) and afternoon (14h00-18h00). Bird fixes were plotted on a 1:25 000 topographic map using GIS ArcMap 10.0 (1999-2010. Individual home range sizes were calculated by minimum convex polygons with 95% of the locations (MCP95) and fixed kernel estimators with 95% probability level (K95) as well as 50% probability level to determine core areas (K50; Worton 1989Worton , 1995.…”
mentioning
confidence: 99%
“…Many species undertake longdistance migrations to avoid harsh winters in the northern temperate region, while lower latitudes have a greater proportion of sedentary species (Chesser, 1998;Newton & Dale, 1996a, 1996b. Thus, there are important differences in dispersal ability, life history traits and population demography in species between these regions plus abiotic factors such as climate and productivity which may affect the relative influence of both habitat fragmentation and each of the three mechanisms on species' responses (Betts et al, 2014;Newbold et al, 2013;Rivera-Ortíz et al, 2015). Therefore, geographic biases in research effort, especially when they occur in conjunction with a bias towards a particular mechanism, have the potential to hamper our ability to draw broad conclusions and develop appropriate conservation strategies accordingly.…”
Section: Geographic and Taxonomic Biasesmentioning
confidence: 99%
“…For instance, adding corridors (linear strips of habitat) or stepping stones (small patches or isolated trees) to the matrix could help both long-range dispersal and multiple-patch use within a home range (Fischer & Lindenmayer, 2002;Saura, Bodin, & Fortin, 2014). A few, well-placed connections across a broad region may be enough to kick-start demographic or genetic rescue (Miquelle et al, 2015), but a greater number of connections within a more confined area may be needed if resource access is to be improved throughout multiple home ranges (Keeley, Beier, Keeley, & Fagan, 2017;Newmark, Mkongewa, & Sobek, 2010).…”
Section: Limited Resource Accessmentioning
confidence: 99%
“…At least four valid location-points were collected per hour (Sechrist and Ahlers, 2003;Newmark et al, 2010). Overall, we attempted to collect a minimum of 100 points/telemetered cuckoo over the course of its period of residence on the Middle Rio Grande (ca.…”
mentioning
confidence: 99%